DEVELOPMENT POINTS OF THE FACTOR ANALYSIS OF THE PROFIT TAX OF COMMERCIAL BANKS (Proceedings of International Conference on Scientific Research in Natural and Social Sciences, 2024)
In this article, the optimization of tax payments in commercial banks by law, including the necessity of stable analysis, is given sufficient importance to improve the methods of calculation and analysis of tax payments in commercial banks from the scientific side.